THE STRATEGIES IN PRESENTING LEXICAL EQUIVALENCE IN C. S. LEWIS'S THE CHRONICLE OF NARNIA: THE LION, THE WITCH, AND THE WARDROBE - Yusti Fargianti, - (2009)
This study is intended to find the strategies in presenting lexical equivalence used by translator in translating lexical items of dialogue in the novel. In addition, it is aimed to show how the strategies are applied in the translation. The study used qualitative method to analyze the data of lexical items of dialogue found in English novel and translated novel. There are approximately 856 lexical items which are analyzed in this study. It is divided into two categories of known and unknown data. The known data consist of 647 items and 209 items for the unknown data. In the end of the study, the writer found that all strategies are used by the translator in translating the lexical items in the dialogue of the novel. It may occur since there are numbers of words which are translated idiomatically. Consequently, the translator used the strategies in presenting lexical equivalence in order to find the appropriate word to convey the meaning.